ANALISIS MISKONSEPSI PADA MATERI ORGAN PERNAPASAN MANUSIA DI KELAS V SDN CIBATU - Fauziah, Ashfi Nurul; Akhmad Nugraha; Pidi Mohamad Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Low understanding of concepts continues to be a problem in the world of education. Students' ability to understand concepts is very important because concepts are the basis for thinking to define and differentiate objects which can reduce conceptual errors. The aim of this research is to analyze students' misconceptions about human respiratory organs in class V at SDN Cibatu and find out the causes of students' misconceptions about human respiratory organs at class V at SDN Cibatu, as well as provide recommendations for overcoming the problem of students' misconceptions about human respiratory organs. in class V at SDN Cibatu. This research uses a qualitative approach with descriptive methods. The subjects in the research were 24 class V students at SDN Cibatu. The data collection techniques include observation, tests, interviews and documentation. The results of this research indicate that there are misconceptions among class V students at SDN Cibatu. The most common misconception in question number 2 was regarding the function of the pharynx with a percentage of 83%. The things that cause students' misconceptions come from the students themselves, namely wrong preconceptions, wrong intuition, students' associative thinking, and students' lack of ability. Apart from that, the reason students come from educators.